Alpha-1 Antitrypsin Prevents the Development of Preeclampsia Through Suppression of Oxidative Stress - Feng, Yaling; Xu, Jianjuan; Zhou, Qin; Wang, Rong; Liu, Nin; Wu, Yanqun; Yuan, Hua; Che, Haisha (Frontiers in Physiology, 2016)
Preeclampsia (PE) and its complications have become the leading cause of maternal and fetal morbidity and mortality in the world. And the development of PE is still barely predictable and thus challenging to prevent and manage clinically. Oxidative stress contributes to the development of the disease. Our previous study demonstrated that exogenous Alpha-1 antitrypsin (AAT) played a cytoprotective role in vascular endothelial cell by suppressing oxidative stress. In this study, we aim to investigate whether AAT contributes to the development of PE, and to identify the mechanism behind these effects. We found that AAT levels were significantly decreased in placenta tissues from women with PE compared that of healthy women. Notably, we demonstrate that AAT injection is able to relieve the high blood pressure and reduce urine protein levels in a dose-dependent manner in PE mice. In addition, our results showed that AAT injection exhibited an anti-oxidative stress role by significantly reducing PE mediated-upregulation of ROS, MMP9 and MDA, and increasing the levels of SOD, eNOS and GPx with increased dosage of AAT. Furthermore, we found that AAT injection inactivated PE mediated activation of PAK/STAT1/p38 signaling. These findings were confirmed in human samples. In conclusion, our study suggests that exogenous AAT injection increases the antioxidants and suppresses oxidative stress, and subsequent prevention of PE development through inactivation of STAT1/p38 signaling. Thus, AAT would become a potential strategy for PE therapy.